Occurrence and extracellular enzyme potential of Actinomycetes of a thermoltalerant, northern region of Karanataka, Inida - Nayaka, Sreenivasa; M, Vidyasagar G (International Multidisciplinary Research Journal, 2013)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif][if gte mso 9]> <![endif][if gte mso 10]> <![endif]--> Occurrence and extracellular enzyme activities of a thermotalerent actinomycetes isolated from thermal spring of compost pit area, hair, feathers dumping places and municipal wastes of Gulbarga and Bellary (Northern part of Karnataka) and tested their degradability against hair and feather. A total of 67 actinomycetes were isolated, out of these 57 actinomycetes screened exhibited amylase, protease, chitinase, cellulase and keratinase activity determined in the petriplate using on starch casein agar (SCA) and nutrient agar media (NA). Out of 57 actinomycetes, 50 isolates showed amylase, 54 protease, 50 chitenase, 52 cellulase and 41 isolates showed keratinase activities respectively. The Maximum keratinase activity shows VSAC-12, this study shows that the isolates were found to be capable using keratin substrates as sole source of carbon and energy for further investigation.